2013
DOI: 10.1093/eurheartj/eht100
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging-defined areas of microvascular obstruction after acute myocardial infarction represent microvascular destruction and haemorrhage

Abstract: The contrast-devoid core of revascularized STEMI contains extensive erythrocyte extravasation with microvascular damage. Attenuating the reperfusion-induced haemorrhage may be a novel target in future adjunctive STEMI treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
117
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(139 citation statements)
references
References 37 publications
12
117
3
1
Order By: Relevance
“…4 Histologically, we found that the infarcts had a core consisting of hemorrhage and microvascular destruction that corresponded perfectly with the regions denominated as microvascular obstruction area on MRI. This leads us to believe that microvascular obstruction as currently defined by the contrast-devoid areas on late-gadolinium MRI and intramyocardial hemorrhage as determined by T2-weighted imaging in fact depict the same histological substrate.…”
Section: To the Editorsupporting
confidence: 69%
“…4 Histologically, we found that the infarcts had a core consisting of hemorrhage and microvascular destruction that corresponded perfectly with the regions denominated as microvascular obstruction area on MRI. This leads us to believe that microvascular obstruction as currently defined by the contrast-devoid areas on late-gadolinium MRI and intramyocardial hemorrhage as determined by T2-weighted imaging in fact depict the same histological substrate.…”
Section: To the Editorsupporting
confidence: 69%
“…Myocardial hemorrhage reflects the aggregation and extravasation of erythrocytes4, 20, 45 and is a manifestation of severe microvascular injury. On CMR at day 3, 5 patients without evidence of hemorrhage on T2* imaging had hypointense cores on T2 maps and microvascular obstruction on contrast imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results confirm that infarct pathologies evolve progressively after MI and thus may be amenable to targeted preventative therapeutic interventions. Robbers et al45 proposed that myocardial hemorrhage was the final consequence of severe microvascular thrombosis and that therapeutic interventions that restored microvascular perfusion might, in turn, prevent myocardial hemorrhage. Observations in the current study (Table 2; Figure 3) and by Robbers et al45 and Payne et al20 also support the notion that red blood cells may be “trapped” in the microcirculation of the culprit coronary artery, reflecting a contributing cause and/or consequence of microvascular obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…12 Again, ischemia followed by reperfusion can disrupt the endothelial barrier and damage the microvasculature, facilitating extravasation of blood cells upon reperfusion and eventually causing intra-myocardial hemorrhage (IMH). 13 Of note, patients with this more severe form of CMVO seem to have a worse outcome than patients with CMVO but without IMH. 14 A third important mechanism of CMVO is represented by distal physical and chemical substances embolization.…”
Section: Mechanisms Of Coronary Microvascular Obstructionmentioning
confidence: 95%
“…Of note, CMR may give additional hints to the presence of IMH. 13,14 Other imaging techniques under investigation for CMVO detection include myocardial scintigraphy or hybrid positron emission tomography-computed tomography. 35 …”
Section: No-invasive Indexes Of Coronary Microvascular Obstructionmentioning
confidence: 99%